2019
DOI: 10.1002/gps.5077
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy improves diverse profiles of depressive symptoms in Parkinson's disease

Abstract: Objective Depression is among the most common and debilitating nonmotor complaints in Parkinson's disease (PD), yet there is a paucity of controlled research to guide treatment. Little research has focused on the extent to which specific depressive symptom profiles may dictate unique clinical recommendations to ultimately improve treatment outcomes. The current study examined the impact of cognitive behavioral therapy (CBT) on different types of depressive symptoms in PD. It was hypothesized that the cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…Though the small number of participants not taking antidepressant medications (n = 22 [30%]) also precludes meaningful exploratory analyses of the effect of ADM on T-CBT response in the current study, evidence from prior work (with a more balanced sample with respect to ADM use) reflected greater benefits of antidepressants for somatic symptoms of dPD only, in the context of combined treatment. 47 In addition, prior research has shown that caregiver involvement in dPD treatment enhances patient response, 48 indicating a need for further investigation into the nature and magnitude of this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the small number of participants not taking antidepressant medications (n = 22 [30%]) also precludes meaningful exploratory analyses of the effect of ADM on T-CBT response in the current study, evidence from prior work (with a more balanced sample with respect to ADM use) reflected greater benefits of antidepressants for somatic symptoms of dPD only, in the context of combined treatment. 47 In addition, prior research has shown that caregiver involvement in dPD treatment enhances patient response, 48 indicating a need for further investigation into the nature and magnitude of this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings parallel our prior RCT of CBT for dPD, in which targeted cognitive and behavioral symptoms improved more than somatic symptoms. 47 Finally, while remote delivery of interdisciplinary PD services is growing and increasingly recognized as critical for advancing care, limitations remain on insurance coverage for telemental health services like T-CBT. At this time, 36 states and Washington, DC, require private insurers to provide coverage parity for in-person and telemedicine-delivered care, while 21 states and Washington, DC, have such policies in Medicaid, 49 with the availability of specific telemental health services subject to states' scope-of-practice laws.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of emotional problems in PD, the most effective seem to be anxiety and depression CBT protocols [152,153] performed independently or combined with pharmacotherapy [154]. Most of the interventions already reported took place in groups or were telephone-based [152].…”
Section: Cognitive Pd Rehabilitationmentioning
confidence: 99%
“…Parkinson’s disease (PD) is an extrapyramidal syndrome characterized by muscle stiffness, tremors, and bradykinesia that can evolve to loss of motor control, tremors at rest, and postural instability. Other symptoms may be depression and slowness in speech [1,2].…”
Section: Introductionmentioning
confidence: 99%